Acute responses of inflammatory markers, glucose, and myoglobin in blood following neuromuscular electrical stimulation - Johanna Flodin; Parsia Amiri; Stefan M. Reitzner; Aisha S. Ahmed; Paul W. Ackermann (European Journal of Applied Physiology, 2026)
Purpose Physical inactivity contributes to systemic inflammation and metabolic dysfunction. Neuromuscular electrical stimulation (NMES) offers an alternative to exercise for individuals unable to perform voluntary physical activity. This study investigated whether a single submaximal NMES session alters inflammation-related proteins, muscle-damage markers and glucose levels in healthy adults. Methods Thirty-six healthy adults underwent a 2-hour NMES-session targeting the quadriceps, hamstring and gluteal muscles using wearable NMES-pants. Stimulation was delivered at individually tolerated intensities (visual analogue scale, (0–10), < 4). Venous blood samples were collected immediately before and after NMES. Inflammatory proteins and myoglobin were quantified using OLINK multiplex proteomic panel (92 proteins), and metabolic markers including glucose, lactate, pH and electrolytes were assessed using standard laboratory methods. Results Of the 92 inflammatory proteins analyzed, 13 were nominally affected by NMES. After correction for multiple comparison, FMS-like tyrosine kinase 3 ligand (Flt3L) and fibroblast growth factor 19 (FGF19) remained significantly downregulated (Flt3L: 9.45 ± 0.12 to 9.11 ± 0.17, p < 0.001; FGF19; 9.43 ± 0.88 to 8.80 ± 0.84, p < 0.001; both normalized protein expression (NPX)). Myoglobin increased (7.70 ± 0.50 to 8.24 ± 0.83 NPX; p < 0.001), while blood glucose decreased modestly (5.35 ± 0.73 to 5.17 ± 0.36 mmol/L; p = 0.039). Lactate, pH, sodium and potassium remained unchanged. Conclusion A single submaximal NMES-session elicited acute systemic responses characterized by downregulation of key inflammation-related proteins, mild myoglobin elevation and lower glucose levels – changes that mirror patterns observed after moderate exercise. These findings suggest that NMES at well-tolerated submaximal intensities can induce metabolic adaptations and may represent a safe, exercise-mimicking intervention to counteract inflammation and metabolic dysfunction in individuals with limited physical activity.